User communities: From nice-to-have to must-have - Joana Costa; Inês Amorim; Jo\~ao Reis; Nuno Mel\~ao (Journal of Innovation and Entrepreneurship, 2023)
With Industry 5.0 already on the horizon, firms need to adapt their strategies to better cater to an increasingly demanding and sustainability-conscious customer base. At the same time, the role of customers has shifted from being mere passive buyers to active users, who not only demand personalized products and services to suit their needs and preferences, but also actively engage other users and stakeholders, thereby grounding the Quadruple Helix model. The objective of this paper is to assess the role of user communities in fostering firms' innovation in all types of innovation. Econometric estimations identified the user community as a driver of innovation propensity. Additionally, the relevance of these communities across all types of innovation (mainly for product and process innovation) was proven. Robustness analysis confirmed the results obtained in different dimensions and established a connection to human capital. This finding revealed that absorptive capacity serves not only as a facilitator of innovation, but also as a moderator. The empirical contributions point towards the urgency of policy actions that consistently involve these agents as vehicles of responsible innovation, which can fine-tune the innovation paths towards an eco-friendlier innovation ecosystem. Further testing the connection between human capital and the user community is required, as the establishment of efficient communication channels promoting the knowledge flows inside the firm will leverage innovation outputs in the different innovation types.
Keywords: 650; Open innovation; CIS; Industry 5.0; Logit models; Quadruple Helix model; User communities